Two new species of Anomaloglossus (Anura: Aromobatidae) of the stepheni group from Suriname - Fouquet, Antoine; Jairam, Rawien; Ouboter, Paul; Kok, Philippe J. R. (Zootaxa, 2020)
Anomaloglossus is a species-rich genus of frogs endemic to the Guiana Shield that still harbours several unnamed species. According to a recent integrative taxonomic survey, the A. stepheni species group includes five valid nominal species and at least four putatively unnamed species, two in Brazil and two in Suriname. In this paper, we describe the two species from Suriname based on adult and tadpole morphology as well as their calls and natural history. Both have exotrophic tadpoles transported by the male to small water bodies. These two new species differ from each other and from other congeners in body size, colouration pattern, call characteristics and breeding sites. Both have narrow distributions and should be considered Endangered according to IUCN criteria.